Study of Management Role and Nurses Mental Hea lth in General Hospitals in Tehran - Rakhshandeh Mohammadi (Iran University of Medical Sciences, 1998)
This was a correlational study with its primary aim to study the relation between management role and nurses mental health in general hospitals in Tehran. 574 Nurses and 53 managers were surveyed in this study. Two. types of questionnaires were distributed among them. Nurses questionnaire consisted of 4 parts, i.e.demographic data, different aspects of job satisfaction, mental health and factors involved in creation of stress and levels of stress at work. Managers questionnaire dealt with demographic data, different factors related to their function and finally, three open questions regarding managers recommendations were posed. The findings showed that the majority of nurses, who belonged to age group between 20-24, were women holding B.S. degree and with less of than 10 years of work experience. Half of them were working rotating shifts and a high percentage of them were working extra shifts. It was also revealed that the majority of managers were over 46 years of age and married, had a B.S. degree with 21 years of work experience. They had completed two terms of management training units, but with less than 5 credits. The findings also showed that nurses job satisfaction (57.29%), was almost negligible. 29.58 percent of all nurses, based on "almost high" and "very high" scale carried symptoms of nonmental health. The majority of them (62.4%) complained of stress at work. But managers believed that their efficiency, from different points of view, was almost high and very high (93%). The findings also revealed that there existed a meaningful and direct correlation among physical, welfare, social, mental, educational and managerial and supervisory factors related to job satisfaction and also with the general demographic of the incumbent. It was also found that the correlation between different aspects of mental health and overall demographic factor was meaningful. It was also found that the greatest degree of correlation existed between managerial and supervisory factors and all social factors related to job satisfaction and managerer ' s function obtained. Other factors, such as anxiety, sleep disorder with depression symptoms and psycho-somatic disorder were also observed. Overall the average for managerial and supervisional  with job satisfaction factors and managers function and managers function and the average for social dysfunction with nurses mental health, in comparison with other factors, were consideraly high. Path analysis was applied, and a meaningful and direct correlation between nursing service managers and hospital's manager, on one hand, and an indirect correlation with nurses stress, on the other hand were obtained. Based on the findings, some recommendations for future studies and application of the [mdings were made.